The Communicative Work of Biology-Journal Captions: Lessons for Technical and Professional Communication. Issue 4 (1st October 2016) - Smith, Jordan; Mackiewicz, Jo; Hanson, Derek; Fanning, Shannon N.; Doan, Sara
ABSTRACT: The authors examined a corpus of figure captions from technical and professional communication (TPC)-journal articles to test their sense that TPC captions do not fulfill their communicative potential as well as, they sensed, journals in science often do. The authors performed a content analysis on captions from biology-journal articles and iteratively tested a coding scheme of caption content. The resulting scheme can help in analyzing caption content, developing captions, and imparting a variety of TPC-related skills to students.